Moral Education in the View of Yunahar Ilyas - Sufri Situmorang, Jamaluddin; Akrim, Akrim; Harfiani, Rizka (Lafadz Jaya Publisher, 2025)
This study examines the concept of moral education in the view of Yunahar Ilyas and its relevance in Indonesia. Moral education is an integral part of Islamic teachings, occupying a special and very important position, as evidenced by the many verses of the Qur'an and the hadith of the Prophet that discuss it. The concept of morality itself etymologically means character, temperament, behavior, or nature, which regulates human relations with God, others, and the universe. This study uses a qualitative method with a library research approach, collecting data from written materials such as books, journals, and articles, with the book